Sh. Shaxs va uning ekstremal vaziyatlarda qaror qabul qilishning individual psixologik jixоtlari - Najmiddinova, M (SCIENCE and SOCIETY, 2025)
This article examines the psychological aspects of decision-making in various extreme situations based on personality, individual psychological characteristics and in accordance with psychological approaches, decision-making is, on the one hand, cognitive, regulatory, communicative in nature, on the other - a socio-psychological phenomenon that is fundamental for further actions of an individual in the biosphere.
Keywords: personality and psyche; individuality; situational situations; social adaptation; social maladaptation; social environment; megafactors; mezzo-factors; the course of biochemistry; personality and archetypes; personality and its individual psychological characteristics decision-making; decision-making; cognition; communication; professional activity